Increased Numeracy Skills of Children with Snakes and Ladders Game - Fidrayani Fidrayani; Rina Syafrida; Puspa Ayu Melodyana (Journal of Early Childhood Education (JECE), 2020)
This research aims to improve the ability to count 4 - 5 years old children with snakes and ladders in group A PAUD Dahlia. The method used in this research is collaborative classroom action research using Kemmis and Mc Taggart's models. CAR is implemented as an effort to overcome problems that arise in the classroom. Method is carried out in four stages, are planning, action, implementation, and reflection. The subjects of the study were students of group A PAUD Dahlia, ten (n=10) children. The object of this study is the ability to count 4 - 5 years old children. Data collection method used is observation. Technical data analysis was done in a descriptive qualitative and quantitative manner. The established success indicator is that at least 75% of 10 children reach the counting ability. This research was conducted in two cycles. The results of the study indicate that the numeracy skill has increased. Increased numeracy skills can be seen from the indicator ability to count objects 1-10, recognize the concept of numbers, recognize symbols 1-10, mention symbols 1-10, matching numbers with symbol numbers. Increased numeracy skills of children aged 4-5 years with snakes and ladders in the implementation of pre-action 31, 5%, and in the first cycle increased to 51.5%, because it is still less than the success criteria that should be carried out then the next action is cycle II and increased greatly good by getting a percentage of 85%. Many games for children was suggested for increase numeracy skills.